Transdermal delivery of PeptiCRAd cancer vaccine using microneedle patches - Carmine D'Amico; Manlio Fusciello; Firas Hamdan; Federica D'Alessio; Paolo Bottega; Milda Saklauskaite; Salvatore Russo; Justin Cerioni; Khalil Elbadri; Marianna Kemell; Jouni Hirvonen; Vincenzo Cerullo; et al. (Bioactive Materials)
Microneedles (MNs) are a prospective system in cancer immunotherapy to overcome barriers regarding proper antigen delivery and presentation. This study aims at identifying the potential of MNs for the delivery of Peptide-coated Conditionally Replicating Adenoviruses (PeptiCRAd), whereby peptides enhance the immunogenic properties of adenoviruses presenting tumor associated antigens. The combination of PeptiCRAd with MNs containing polyvinylpyrrolidone and sucrose was tested for the preservation of structure, induction of immune response, and tumor eradication. The findings indicated that MN-delivered PeptiCRAd was effective in peptide presentation in vivo, leading to complete tumor rejection when mice were pre-vaccinated. A rise in the cDC1 population in the lymph nodes of the MN treated mice led to an increase in the effector memory T cells in the body. Thus, the results of this study demonstrate that the combination of MN technology with PeptiCRAd may provide a safer, more tolerable, and efficient approach to cancer immunotherapy, potentially translatable to other therapeutic applications.